Minimally Invasive Treatment Options for Managing Spontaneous Intracerebral Hemorrhage. Issue 1 (January 2021) - Kim, Michael; Cooper, Jared; Al-Mufti, Fawaz; Gandhi, Chirag; Bowers, Christian
Abstract : Spontaneous intracerebral hemorrhage (SICH) is a common stroke subtype, accounting for 10–35% of all stroke. It is the most disabling subtype as well, with disproportionately high rates of morbidity and mortality. Despite numerous advances in neurocritical care and stroke management, the prognosis remains poor, and no medical or surgical interventions have been shown to significantly reduce mortality or improve outcomes. Surgical evacuation of SICH has many theoretical benefits, such as reducing secondary injury, reducing intracranial pressures, and preventing cerebral herniation. However, trials involving open craniotomy for SICH evacuation have not yielded significant clinical benefit, and one thought is that benefit is not seen due to injury to the overlying healthy brain tissue. Therefore, minimally invasive options have increasingly been studied as an option to evacuate the SICH while minimizing injury to healthy tissue. We present here a select review of various minimally-invasive techniques for the evacuation of SICH.